Penggunaan Metode Teka-Teki dalam Pembelajaran Anak Autis Hiperaktif di Sekolah Luar Biasa Putra Manunggal Gombong Kebumen - annafi, Ni'matul Nur; Khomsatun, Khomasun; Jannah, Vida Nurul; Setiyani, Sulis; Fatimah, Siti; Murtajib, Ahmad (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
This research aims to explore the experience of using the puzzle method in learning children with hyperactive autism (attention deficit hyperactivity disorder/ ADHD) in a special education environment. The method used in this research is a descriptive qualitative method to explore the perspectives of hyperactive autistic children and educators regarding the implementation and impact of using this method on their learning. The aim of this research is a puzzle model learning method that can help restore the focus of attention of ADHD children. The research subjects consisted of one hyperactive autistic child and two teachers at the Putra Manunggal Gombong Special School (SLB). The data collection technique used is learning observation, interviews and documentation techniques. The background to this research is that this observation provides in-depth insight into the potential and limitations of the puzzle method as a learning approach for hyperactive autistic children in a special education context, as well as the application of methods that focus on improving the quality of social interactions and children's independence in an educational environment. The results of the research show that the use of the puzzle method can increase the involvement of hyperactive autistic children in learning, improve the focus of the child's attention and increase the child's social interactions with other friends. In implementing this method, there are challenges that also arise, such as the need to meet children's individual needs and the integration of the method with the special education curriculum.